Salmonella Enteritidis infection in young broiler chickens from breeding farm: A case report - Poernomo, Sri; Rumawasz, Indrawati; Sarosa, A (Indonesian Journal of Animal and Veterinary Sciences, 1997)
old from a breeding farm not far from Bogor. Samples were examined pathologic anatomically (PA) and bacteriologically to isolate the causative agents . The sensitivity of the main causative agents isolated from the samples was tested with some drugs, while its pathogenicity was tested in 3 days old chickens intramuscularly, subcutaneously, intraperitoneally and orally, three chickens per inoculations . Exudative and caseous omphalitis, pericarditis, hepatitis, sirsacculitis, and coxofemoral and knee joints were observed in PA examinations, while on bacteriological examination the main cusative agent, ie. Salmonella Enteritidis was isolated successfully . Drug sensitivity test showed that the pathogen was sensitive to chloramphenicol, baytril, gentamisin, and sulphametoxazole-trimethoprim, and resistant to erythromycin, colistin, streptomycin and kanamycin . On the other hand, pathogenicity test of the isolate showed that all but two chickens which were inoculated orally, were died 24 hours post-inoculation . It was concluded that young broiler chickens of the farm were infected by Salmonella Enteritidis. Â  Keywords : Salmonella Enteritidis infection, broiler chickens, breeding farm